Evaluation of the CIPP Model in Islamic Religious Education Learning at SMPN 8 Samarinda for Student Character Development - Muhamad Ayul Ginoga; Zurqoni Zurqoni; Sugeng Sugeng (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to evaluate Islamic Religious Education (PAI) learning in developing students’ character at SMP Negeri 8 Samarinda using the CIPP (Context, Input, Process, Product) evaluation model. This research employed a qualitative approach with an evaluative research design. Data collection techniques were conducted through observation, interviews, and documentation involving the principal, Islamic Religious Education teachers, and students as research subjects. Data analysis used the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results showed that in the context aspect, PAI learning had been aligned with the Merdeka Curriculum and students’ character development needs through various religious habituation activities at school. In the input aspect, the learning process was supported by learning tools, varied teaching methods, digital learning media, and adequate teacher competence, although there were still limitations in learning facilities and infrastructure. In the process aspect, learning activities were carried out actively and interactively through discussions, question-and-answer sessions, presentations, worship practices, and the habituation of character values in daily learning activities. Meanwhile, in the product aspect, PAI learning had a positive impact on students’ character development, particularly in religious attitudes, discipline, responsibility, and politeness. Based on the findings, it can be concluded that Islamic Religious Education learning at SMP Negeri 8 Samarinda has been implemented quite effectively in supporting students’ character development based on the CIPP evaluation model. However, improvements are still needed in learning facilities, equal student participation, and sustainable character development programs.